Acute bouts of wheel running decrease cocaine self-administration: Influence of exercise output - Smith, Mark A.; Fronk, Gaylen E.; Zhang, Huailin; Magee, Charlotte P.; Robinson, Andrea M. (Pharmacology, biochemistry and behavior, 2016)
Exercise is associated with lower rates of drug use in human populations and decreases drug self-administration in laboratory animals. Most of the existing literature examining the link between exercise and drug use has focused on chronic, long-term exercise, and very few studies have examined the link between exercise output (i.e., amount of exercise) and drug self-administration. The purpose of this study was to examine the effects of acute bouts of exercise on cocaine self-administration, and to determine whether these effects were dependent on exercise output and the time interval between exercise and drug self-administration. Female rats were trained to run in automated running wheels, implanted with intravenous catheters, and allowed to self-administer cocaine on a fixed ratio (FR1) schedule of reinforcement. Immediately prior to each test session, subjects engaged in acute bouts of exercise in which they ran for 0, 30, or 60min at 12m/min. Acute bouts of exercise before test sessions decreased cocaine self-administration in an output-dependent manner, with the greatest reduction in cocaine intake observed in the 60-min exercise condition. Exercise did not reduce cocaine self-administration when wheel running and test sessions were separated by 12h, and exercise did not reduce responding maintained by food or responding during a saline substitution test. These data indicate that acute bouts of exercise decrease cocaine self-administration in a time- and output-dependent manner. These results also add to a growing body of literature suggesting that physical activity may be an effective component of drug abuse treatment programs.